A szabad akarat és az eleve elrendelés a korai muszlim racionális filozófiában - Rugási, Gyula (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
Dawud al-Muqammas, the elder colleague of the much better known Sadia Gaon, the first prominent figure in medieval Jewish philosophy, wrote his major work Isrún-Maqalat (Twenty Chapters) at the end of the 9th century, which was preserved in a manuscript discovered in the National Library of St Petersburg at the end of the 19th century, although not in its entirety. The work was written in Arabic, as was the custom of the time, and forms an integral part of the intellectual-historical fluid known as the (mutazilite) kalam. The world over languages and religions, which was the golden age of Muslim and Jewish philosophy – approximately the 10th-12th centuries – could perhaps be called rational theology in scholastic terms. A particular feature of the genre is that its representatives, from the Pyrenees to modern-day Afghanistan, pondered the same problems: the uniqueness of God, his transcendence, his purely pneumatic character, in short, the borderline questions of revelation and Hellenic philosophy. The main work of Al-Muqammas, especially its 11th chapter, interprets a very complex issue, the relations between predestination and free will in a Jewish, Muslim and Syriac Christian context, attempting to overcome the contradictions that these three religions, and especially Islam, brought to the surface again and again at the turn of the 9th and 10th centuries.